Avaliação de revestimentos de argamassa à permeabilidade ao vapor de água - Temp, Aldo Leonel (2014)
The present study evaluates: the performance of tensile adhesion and water and vapour permeability of mortar rendering systems.The study can highlight the following conclusions: the traditional cement, lime and sand mortars presented the lower adherence values and the highest water absorption values independent of the substrate used - loadbearing ceramic masonry block, nonbearing block with smooth surface and nonbearing block with rugged surface; through the results of the experiments it can be recommended the use of the corse mortar as the basis of the coating system to increase the adhesion and water permeability; the presence of the coarse layer elevated the adherence capacity of all mortars tested but no significant change was noticed in the water absorption; Generally the loadbearing ceramic masonry blocks presented the lower values of water absorption; the nonbearing rugged blocks showed higher adherence levels than the smooth surface blocks; the water vapour permeability coefficient was determined using a test cup with 100mm and worked well with mortar specimens with 20mm thickness; the industrialized mortars presented scattered results in the water vapour permeability test, prooving that the internal pore structure has influence in the vapour transmission; it was also verified that the ceramic material has a great restriction to vapour transmission because of its microstructure; it was also possible to notice the presence of salts in the surface of the samples, that occurred because the water vapour flow is continuous when interacting with the saline solution of lithium chloride; it was also verified that the mortars present different internal arrangements with pores that have distinct geometries.